Feedback Effects for Epiduroscopy Education based on Serious Game - Jang, Seong-wook; Ko, Junho; Choi, Yujin; Sang Kim, Yoon (International Journal of Engineering and Technology, 2018)
Efficient surgical education is required because epiduroscopy is difficult to learn and need a high-level surgical skill. Recently, serious game has been used in specialized areas such as medical assistance and learning (surgical education). Serious game in surgical education provides a trainee with opportunities to learn a surgical skill outside OR (operating room). Pre-operative virtual experience allows the trainee to be adapted to the patient and OR environment. In this paper, feedback effects for epiduroscopy education based on serious game are studied. The feedback effects (visual, auditory, and tactile feedbacks) were examined for the epiduroscopy education based on serious game with respect to three methods.Â Â